The grammatical intensification signals in English and Bicol adjectives and adverbs a contrastive analysis - Sta. Maria, Lourdes Dinio 1943- (1969)
The special problem presents a descriptive-contrastive analysis of the grammatical intensification signals in English and Bicol adjectives and adverbs. The study is made for the purpose of finding out the cause of the excessive use of "very" by Bicol learners of English intensification signals.
Vita.
Thesis (M. Ed. Second Language Teaching)--University of the Philippines, Diliman.
Keywords: English language -- Adjective; English language -- Adverb; English language -- Grammar, Comparative -- Bicol